2020
DOI: 10.15587/1729-4061.2020.205474
|View full text |Cite
|
Sign up to set email alerts
|

A study of the electrolyte composition influence on the structure and properties of MAO coatings formed on AMg6 alloy

Abstract: Досліджено вплив умов електролізу при різних складах електроліту на фазоутворення і властивості покриттів, отриманих мікродуговим оксидуванням (МДО) на алюмінієвому сплаві АМг6. Для електролізу використовувалися електроліти трьох типів: лужний електроліт (розчин (КОН) в дистильованої воді), силікатний електроліт (з різним процентним вмістом Na 2 SiO 3 складової) і комплексний лужно-силікатний електроліт з вмістом рідкого скла (1÷12 г/л Na 2 SiO 3) і гідроксиду калію (1÷6 г/л КОН). Аналіз отриманих результатів … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The use of a high content of liquid glass in electrolytes 6 and 7 is accompanied by the appearance of a halo-like component in the diffraction spectra. This is due to the formation of a very finely dispersed phase under the action of silicon [20]. For these types of electrolytes, MgAl2O4 and Mg2SiO4 are identified as accompanying phases.…”
Section: Resultsmentioning
confidence: 99%
“…The use of a high content of liquid glass in electrolytes 6 and 7 is accompanied by the appearance of a halo-like component in the diffraction spectra. This is due to the formation of a very finely dispersed phase under the action of silicon [20]. For these types of electrolytes, MgAl2O4 and Mg2SiO4 are identified as accompanying phases.…”
Section: Resultsmentioning
confidence: 99%
“…Al 3+ ions are statistically distributed over 8 tetrahedral and 16 octahedral positions. Therefore, the structure of γ-Al 2 O 3 is called a defect-type spinel structure, and upon exposure to temperature, redistribution of Al 3+ ions over octahedral and tetrahedral positions can occur, which affects the lattice period and properties [39,40]. Such a crystal lattice is unstable and its existence requires stabilizers in the form of ions of different elements.…”
Section: Discussion Of the Results Of The Electrolysis Conditions Effmentioning
confidence: 99%
“…Based on the analysis of the results for different oxidation modes [27,30,39,40], three modes were chosen as suitable for obtaining homogeneous coatings for further studies: 1) electrolyte composition 1:6 (1 g/L KOH and 6 g/L Na 2 SiO 3 ), current density j=20 A/dm 2 , τ=180 min, electrolyte temperature t=20 °C;…”
Section: Materials and Methods For Studying The Effect Of Electrolysimentioning
confidence: 99%
“…%). As follows from a comparison with the results obtained on the microarc oxidation of the AMg6 alloy [48], the use of other elements for alloying can significantly change the formation kinetics of the MAO coating and its phase composition. Therefore, in order to establish universal regularities for different types of aluminum alloys, further studies are required, which imply the determination of regularities in the structural-phase transformations of MAO coatings on aluminum alloys with metals, for which the oxidation energy is higher than for copper (V, Nb, Ta, and Cr).…”
Section: Phase Composition and Properties Of Mao Coatings During Omentioning
confidence: 91%
“…It should also be noted that the early results obtained for the AMg6 alloy, where Mg was the main alloying element (up to 5.8 %), showed that the γ−Al 2 O 3 →α−Al 2 O 3 transformation did not occur at all under similar conditions [48]. Thus, alloying of aluminum with copper is an important factor for the γ−Al 2 O 3 →α−Al 2 O 3 transformation.…”
Section: Phase Composition and Properties Of Mao Coatings During Omentioning
confidence: 94%